Peran Mediasi MargPeran Mediasi Margin Laba Bersih pada Faktor Internal terhadap Rentabilitas Perusahaan Sektor Teknologi yang Terdaftar di BEI Tahun 2021-2024 in Laba Bersih pada Faktor Internal terhadap Rentabilitas Perusahaan Sektor Teknologi yang Terdaftar di BEI Tahun 2021-2024 - Rihadatul Aisy, Salma; Waskito, Jaka; Amirah, Amirah (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2025)
This inquiry examines the repercussions of Working Capital Turnover, Activity, Liquidity, and Inventory Turnover on Profitability, positioning Net Profit Margin as a mediator within technology enterprises listed on the Indonesia Stock Exchange (2021–2024). A quantitative framework was employed on secondary data sourced from the IDX portal utilizing multiple linear regression and path analysis. Pivotal outcomes elucidate: (1) Partially, Working Capital Turnover manifests no significant bearing on Net Profit Margin or Profitability; Activity exerts a substantially adverse effect on Net Profit Margin yet remains neutral toward Profitability; Liquidity demonstrates significantly positive associations with both variables; Inventory Turnover exhibits markedly negative impacts on Net Profit Margin and Profitability; whereas Net Profit Margin itself evinces no correlation with Profitability; (2) Path analysis discloses Net Profit Margin's efficacious mediation between Working Capital Turnover and Profitability, yet identifies its ineffectiveness in mediating the influences of Activity, Liquidity, and Inventory Turnover upon Profitability.